Increasing Awareness Among Teenagers About Preventing Non-Communicable Diseases Through The Use Of Multimedia At Karang Taruna Wates - Bandhi Prasetya Nugroho; milda, ratna; Fendy Prasetyawan; Baarik Lana Fadli; Yuneka Saristiana; Isma Oktadiana; Arsiaty Sumule (Institut Agama Islam Negeri Ponorogo, 2024)
Non-Communicable Diseases (NCDs) are currently a serious health problem in the world, because these diseases are one of the most common causes of death. Community empowerment in preventing PTM through community components, one of which is youth organizations or youth organizations which have an important role in taking part, is expected to be able to prevent PTM through various more interesting media. The aim of this community service is to provide PTM education through the use of multimedia. The method used is to convey information accompanied by posters, pictures and discussions. After providing education, it is hoped that youth organizations will be able to be more critical about PTM and be able to provide further education to the wider community, especially in the Wates area, by utilizing multimedia. Keywords: Non-communicable diseases, Karang Taruna, Multimedia